Prove that:

cos^{2}A + cos^{2}B – 2 cosA cosB cos(A +B) = sin^{2}(A +B)

LHS = cos^{2}A + cos^{2}B – 2 cosA cosB cos(A +B)

= cos^{2}A + 1 – sin^{2}B - 2 cosA cosB cos(A +B)

= 1 + cos^{2}A – sin^{2}B - 2 cosA cosB cos(A +B)

__We know that cos ^{2}A – sin^{2}B = cos(A +B) cos(A –B)__

= 1 + cos(A +B) cos(A –B) - 2 cosA cosB cos(A +B)

= 1 + cos(A +B) [cos(A –B) – 2 cosA cosB]

__We know that cos(A -B) = cosA cosB + sinA sinB.__

= 1 + cos(A +B) [cosA cosB + sinA sinB – 2 cosA cosB]

= 1 + cos(A +B) [-cosA cosB + sinA sinB]

= 1 - cos(A +B) [cosA cosB - sinA sinB]

__We know that cos(A +B) = cosA cosB - sinA sinB.__

= 1 – cos^{2}(A +B)

= sin^{2}(A +B) = RHS

Hence proved.

16